Diet, physical activity, and body size associations with rectal tumor mutations and epigenetic changes - Slattery, Martha L. (2010)
Diet and lifestyle factors have been inconsistently associated with rectal tumors. It is possible that evaluation of specific tumor markers with these factors may help clarify these associations. In this study, we examine energy contributing nutrients, dietary fiber, BMI (kg/m2), and long-term physical activity with TP53 mutations, KRAS2 mutations, and CpG Island Methylator Phenotype (CIMP) in 750 population-based cases of rectal cancer compared to healthy controls. We observed that high levels of physical activity reduced the risk of having TP53 and KRAS2 rectal tumor mutations. Dairy products rich in fat were associated with an increased risk of CIMP+ tumors (OR 1.88 95% CI 0.92, 3.84), while low-fat dairy products reduced risk of CIMP+ tumors (OR 0.56 95% CI 0.29, 1.09). Omega-3 fatty acids were associated with a twofold increased risk of a CIMP+ tumor. High levels of vegetable intake reduced risk of both TP53 mutations (OR 0.73 95% CI 0.54, 1.00; p trend 0.02) and KRAS2 mutations (OR 0.60 95% CI 0.40, 0.89; p trend<0.01). High intake of whole grains reduced the likelihood of a TP53 mutation (OR 0.74 95% CI 0.56, 0.99), while high intake of refined grains increased the likelihood of a TP53 mutation (OR 1.41 95% CI 1.02, 1.96). Dietary fiber also was associated with reduced risk of TP53 and KRAS2 rectal tumor mutations. Overall, a prudent dietary pattern significantly reduced the likelihood of a KRAS2 tumor mutation (OR 0.68 95% CI 0.47, 0.98; p linear trend 0.03). These data suggest that diet and lifestyle factors are associated with specific types of rectal tumor mutations and epigenetic changes. Findings need confirmation in other studies.